A Case of Renal Transplantation - Muinuddin, G; Paul, SK; Rahman, MH; Jahan, MH; Begum, A; Salam, MA; Hossain, MM (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):214-6.The abstract of this article is available on the PubMed website